Perlindungan Pengetahuan Tradisional Secara Sui Generis Untuk Menyongsong Masyarakat Ekonomi Asean - Muchtar Anshary Hamid Labetubun; Rory Jeff Akyuwen; Marselo Valentino Geovani Pariela (SASI, 2018)
At this time the Asean Economic Community is being held which is a free trade system in ASEAN Countries (Asean Economic Community), so that traditional knowledge is important to be protected by sui generis in Indonesia which causes the absence of legislation who specifically regulates traditional knowledge because it deals with the transfer of technology, economic development and national honor, and attracts investors in the field of research development in Indonesia, one of the countries that has natural resources and human resources in resulting in a variety of traditional knowledge as a feature of local wisdom, traditional knowledge has a very strategic value to be protected by sui generis in the field of intellectual property as a nation's intellectual work. Protection of traditional knowledge requires regulations in order to regulate the use of sharing benefits that are balanced and equitable for people who have the right to traditional knowledge. The current application of the IPR regime is not optimal in its application to protect traditional knowledge especially regarding traditional medicine against violations committed by foreign countries. The impact of legal protection on traditional knowledge is known to other countries, especially the ASEAN Economic Community as a society that values and utilizes traditional knowledge as an increase in regional income.